(untitled) (Medical Forum Monthly, 2020)
Objective: To find out the frequency of CVP line associated thrombosis in patients suffering from end stage renal disease (ESRD) on hemodialysis. Study Design: Cross-sectional / Descriptive study. Place and Duration of Study: This study was conducted at the Department of Nephrology, Nishtar Medical University Hospital, Multan from October 2018 to March 2019. Materials and Methods: A total of 86 adult patients with advanced stage renal failure who were referred or admitted in Nephrology department for insertion of central venous catheter for hemodialysis were studied and screened for catheter related thrombus. Results: Among 86 patients under study, 52 (60.4%) were men and 36 (39.6%) patients were women. Mean age for study population was 46.52 ± 7.34 years. Among 86 patients, 29 (33.7%) were diabetic, 34 (39.5%) were hypertensive, 35 (40.6%) were smokers and 08 (9.3%) had past episode of thrombosis. Mean for the duration of catheter insertion was 82.52 ± 40.87 days and mean for the hemodialysis tenure was 23.46 ± 10.73 months. Significantly high proportion of our study cases i.e. 64 (74.4%) had to go through the process of hemodialysis twicea week. Catheter induced venousocclusion was noted in 28 (32.6%) of our study cases. Conclusion: In our study, we noticed catheter induced venous occlusion was frequent in patients with end-stage renal disease (ESRD). Cather related venous thrombosis in CKD patients was found to have strong association with advanced age, duration of catheter insertion, male gender and dialysis duration.